Unlocking Economic Growth: Insights from Macroeconomic Indicators and Stock Markets Development in Key OIC Countries - Zein, Nurafifah (Jurnal Magister Ekonomi Syariah, 2024)
Indonesia, Malaysia, Bangladesh, Qatar, Turkey and Kuwait show obvious differences in economic structure, level of development and implemented economic policies. The aim of this study is to analyze the impact of macroeconomic indicators and stock market developments on economic growth in OIC member countries in the period 2018-2022. Panel data is used to determine the impact of market capitalization and turnover ratio as indicators of stock market development, along with inflation and foreign direct investment (FDI) as indicators of macroeconomics, on economic growth.The results show that market capitalization has a negative effect on economic growth, while the turnover rate has a positive effect. On the other hand, inflation contributes positively to economic growth, while FDI has no effect on economic growth. Based on these findings, this study suggests that the governments of OIC countries should focus more on proper management of stock markets and macroeconomic variables to support economic growth.